2003
DOI: 10.21273/horttech.13.1.0058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diploid Pollinizer Frequencies on Triploid Watermelon Quality and Yields

Abstract: During the 1999 and 2000 growing seasons in Illinois, studies were conducted to determine the influence of two pollinizers (`Crimson Sweet' and `Fiesta') and three pollinizer frequencies (11%, 20%, and 33%) on `Millionaire' seedless watermelon (Citrullus lanatus) quality and yields. More large-sized [>16 lb (7.2 kg)] `Millionaire' watermelons were produced when `Crimson Sweet' was used as the pollinizer compared to `Fiesta', which resulted in `Crimson Sweet' leading to gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 4 publications
2
32
0
Order By: Relevance
“…Ultimately, field trials are needed to evaluate the effects of low versus high total pollenproducing pollenizers on triploid watermelon fruit set. However, our hypothesis that overall pollen production may be an important factor to consider when selecting a pollenizer is supported, at least in part, by Fiacchino and Walters (2003), who found that 'Crimson Sweet' was a better pollenizer than 'Fiesta'. Based on our data, the pollen production levels of 'Crimson Sweet' were greater than those found for 'Fiesta'.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Ultimately, field trials are needed to evaluate the effects of low versus high total pollenproducing pollenizers on triploid watermelon fruit set. However, our hypothesis that overall pollen production may be an important factor to consider when selecting a pollenizer is supported, at least in part, by Fiacchino and Walters (2003), who found that 'Crimson Sweet' was a better pollenizer than 'Fiesta'. Based on our data, the pollen production levels of 'Crimson Sweet' were greater than those found for 'Fiesta'.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, growers are interested in optimizing the type and density of pollenizers to maximize field space devoted to the production of the more valuable triploid fruit. Recently, NeSmith and Duval (2001) found that triploid fruit set decreased considerably when the distances between pollenizers and triploid plants exceeded 4.6 m. Similarly, Fiacchino and Walters (2003) evaluated two pollenizers and three pollenizer densities (11%, 20%, and 33%) for their effect on triploid fruit set. They concluded that 'Crimson Sweet' was a better pollenizer than 'Fiesta', and that a pollenizer density of 20% to 33% was better than 11%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In triploid watermelon production, diploids are included as a viable pollen source for pollination and fruit set (Kihara, 1951;Rubatzky and Yamaguchi, 1997). To provide sufficient pollen for maximum triploid fruit yield, plants should be planted in a ratio of one pollenizer plant for every two to four triploid plants (Fiacchino and Walters, 2003;Maynard and Elmstrom, 1992;NeSmith and Duval, 2001). The pollenizer cultivar has an effect on the yield of triploid fruit (Fiacchino and Walters, 2003;Freeman et al, 2007b).…”
mentioning
confidence: 99%
“…The pots were spaced 0.8 m between rows and 0.4 m between plants. A 3:1 ratio between triploid and diploid varieties was used in dedicated rows (Fiacchino & Walters, 2003;Dittmar et al, 2009) for seedless watermelon cultivation. Plants were trellised to facilitate management of this crop in a protected environment greenhouse.…”
Section: Site and Agricultural Practicesmentioning
confidence: 99%